Innovations in insuring the poor: Health insurance for the rural poor: Evidence from Cambodia - Levine, David I. (International Food Policy Research Institute, 2009)
A serious injury or illness usually increases medical expenses and often reduces income. Even worse, some short-term health problems can worsen long-term poverty when families sell productive assets such as land or remove their children from school. In theory, health insurance can help reduce asset sales, reduce the need for new loans, increase the quantity and quality of care, and improve health. Unfortunately, rigorous evidence on the impact of insurance is scarce, particularly in developing countries. It is hard to study the effects of insurance because of adverse selection, which occurs because households that expect high healthcare costs have the strongest incentives to buy health insurance. At the same time, if cautious, well-educated, or wealthy people both engage in safe behaviors and value insurance, then voluntary insurance can enjoy positive selection. Thus, finding that insurance correlates with either poor health or high income would tell us little about the causal effects of insurance on health and economic outcomes. In spite of the challenges, several rigorous studies (primarily in rich countries) find that health insurance usually increases access to healthcare. The effect of that increased access on health depends on the value of that care. Scattered results from the United States and other wealthy countries suggest that health insurance usually leads to modest improvements in health. It remains an open question to what extent insurance in developing countries will increase healthcare access and use, reduce financial vulnerability, and improve health outcomes.